Augustow Chase as the Largest Unsettled Crime Committed on Poles after World War II - Basiński, Patryk (Vade Nobiscum, tom XX/2019: Studia z historii politycznej i wojskowej, 2019)
The article describes the Augustow chase, the largest crime on Poles after World War II, carried out in July 1945 in the lands of Suwalki and Augustow. As a result, almost 600 people was died, mainly civilians. The aim of the article was to analyze legal and practical obstacles in the pursuit of the Polish side to account for the so Augustow chase. The research problem was the answer to the question of whether there are real chances of obtaining redress from the Russian side for the events of the Augustow chase on the way of domestic and international court procedures. The author presented the genesis, course and effects of the raid. Then he made an attempt was made to qualify the crime and the current state of the investigation was presented.